Submission Scenarios to the Special Jurisdiction for Peace for People Excluded from Ley de Justicia y Paz: Fields of Application Disquisition (2018)
The first transitional justice attempt in Colombia was the Ley the Justicia y Paz (Law of Justice andThe first transitional justice attempt in Colombia was the Ley the Justicia y Paz (Law of Justice and Peace Law, Law 975 of 2005), as a result of the Ralito Agreement between the Autodefensas Unidasde Colombia and the Colombian government. Later on, with the issuance of Law 1592 of 2012, apossibility arose for excluding members who did not meet the conditions established in the Ley theJusticia y Paz or who did not comply with the commitments acquired by submitting to that  legislation,and for them to continue being investigated and judged with the ordinary jurisdiction. As a result ofthe Peace Agreement between the Fuerzas Armadas Revolucionarias de Colombia (FARC-EP) and theColombian government, the Special Jurisdiction for Peace (JEP) was founded, through which crimescommitted during the armed conflict will be judged. This paper intends to evaluate the possibilityfor ex-combatants of paramilitary groups who, having applied for the Ley the Justicia y Paz andwho were excluded for not fulfilling some of the requirements or for not having complied with theircommitments, may submit to the JEP. The evaluation is done by constructing scenarios with iconiccases of former paramilitaries excluded from the the Ley the Justicia y Paz.